Clinical Case of X-Linked Lymphoproliferative Syndrome Burdened with Hemophagocytic Lymphohistiocytosis and Crohn's Disease - Ekaterina S. Matros; Alena I. Karitskaya (Педиатрическая фармакология)
Background. X-linked lymphoproliferative (XLP) syndrome is hereditary disease with the incidence of 1-3 per 1 million born boys. This clinical case demonstrates a rare picture of XLP type 2 manifestation without prior Epstein-Barr virus.Clinical case description. Boy D., 15 years old, was admitted to Morozovskaya Children's City Hospital with complaints on fever, abdominal pain, loose stools, weight loss. The past medical history included hemophagocytic syndrome (remission) and acute erythema nodosum. We have performed several studies: abdominal ultrasound (hepatomegaly, dynamic changes in the intestine: parts of the small intestine were enlarged and walls were thickened, mass peristalsis, walls of transverse colon and descending colon are thickened up to 5 mm, mesenteric lymphadenopathy), rectosigmoidoscopy (high-activity ulcerative proctosigmoiditis corresponds to Crohn's disease), biochemical and clinical blood tests (active hemophagocytic syndrome), coagulogram (secondary hypocoagulation), myelogram (no data on hemoblastosis or aplastic condition). Virological blood tests (CMV, EBV, HHV-VI): negative. Laboratory and instrumental tests have revealed recurrence of hemophagocytic syndrome and Crohn's disease. The child was consulted by rheumatologist, hematologist, gastroenterologist, geneticist, neurologist, and clinical pharmacologist. The primary immune deficiency disease was suspected in this patient due to his medical history. Molecular genetic study was performed (deletion including the XIAP gene was revealed) and the diagnosis of primary immune deficiency was verified: X-linked lymphoproliferative syndrome type 2. Thus, allogeneic haematopoietic stem cell transplantation (HSCT) was performed.Conclusion. XLP diagnosis and management require multidisciplinary approach. The early diagnosis is crucial due to the high risk of secondary complications development that can significantly worsen the disease's prognosis. Allogeneic HSCT is the only effective treatment for the disease.